Gastric residual volume measurement in the intensive care unit: an international survey reporting nursing practice. Issue 5 (24th July 2018) - Ozen, Nurten; Blot, Stijn; Ozen, Volkan; Arikan Donmez, Ayse; Gurun, Pınar; Cinar, Fatma Ilknur; Labeau, Sonia
ABSTRACT: Background: Gastric residual volume measurement is routinely used to evaluate the feeding tolerance and gastro‐oesophageal reflux in patients receiving enteral feeding therapy in the intensive care unit. However, little supportive evidence for this intervention is available as the usefulness of gastric residual volume measurements in patients receiving enteral feeding therapy in the intensive care is controversial. Aim: The aim of this study was to assess the practice of intensive care unit nurses related to gastric residual volume measurement in patients receiving enteral nutrition. Methods: A survey was conducted among a sample of intensive care unit nurses ( n  = 832) from four hospitals in Turkey ( n  = 182) and attendees of the Annual Congress of the Flemish Society for Critical Care Nurses in Flanders, Belgium ( n  = 650). The survey instrument was developed by the researchers based on the related literature. Results: A total of 480 nurses completed the questionnaire (response rate = 73%). Gastric residual volume is measured by 98·0% of respondents, with wide variations in the frequency of measuring. A 50–200 mL gastric residual volume is considered problematic by 45·5% ( n  = 183) of the participants, and only 18·4% ( n  = 81) reported their practice to be based on a current guideline. Strikingly, more experienced intensive care unit nurses appear to perform gastric residual volume measurements more commonly than their less experienced colleagues ( p  = 0·004), while the practice is more often reported to be performed in Belgium than in Turkey ( p  < 0·001). Conclusion: Gastric residual volume management could be improved by applying current evidence to daily nursing practice. Relevance to clinical practice: Our results show that increased awareness of these guidelines by nurses is needed to reduce inefficient use of working time and resources, streamline clinical practices and improve patient outcomes. Current gastric residual volume measurement guidelines and up‐to‐date, relevant training should be provided to nurses.